1979
DOI: 10.1111/j.1365-2605.1979.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indomethacin on Semen of Infertile Men

Abstract: The effects of long term administration of the prostaglandin inhibitor, Indomethacin, on semen, in 22 infertile men with severe oligozoospermia and/or asthenozoospermia have been studied. Quantitative assessment of semen in the whole group showed improved sperm motility (P < 0.05), normal morphology (P < 0.05) and concentration (P < 0.002) after treatment. Individual qualitative evaluation of semen parameters showed improvement in sperm count in one third and improved motility and morphology in 18 per cent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The results of the study showed that the control group had a higher number of active sperm cells compared to the groups where indomethacin administration occurred. This finding is consistent with previous research that has found that nonsteroidal anti-inflammatory drugs (NSAIDs) can decrease sperm motility [10]. The decrease in active sperm cells may be due to the fact that indomethacin inhibits the production of prostaglandins, which are important for maintaining sperm motility.…”
Section: Fig 6 Effects Of Indocid On Sperm Count Of the Different Groupssupporting
confidence: 92%
“…The results of the study showed that the control group had a higher number of active sperm cells compared to the groups where indomethacin administration occurred. This finding is consistent with previous research that has found that nonsteroidal anti-inflammatory drugs (NSAIDs) can decrease sperm motility [10]. The decrease in active sperm cells may be due to the fact that indomethacin inhibits the production of prostaglandins, which are important for maintaining sperm motility.…”
Section: Fig 6 Effects Of Indocid On Sperm Count Of the Different Groupssupporting
confidence: 92%
“…Among other chemicals known to cause reproductive damage, substances that interfere with arachidonate metabolism, such as nonsteroidal anti-inflammatory drugs (NSAD), are included [13,22,23,28]. Although these agents are widely used for the treatment of frequent diseases, such as muscular pain, headache, and rheumatoid arthritis, there is no conclusive knowledge about their effects on sperm functional activity.…”
mentioning
confidence: 99%
“…In mice, spermatogenesis is increased by prolonged treatment with acetylsalicylic acid (100 or 200 mg/kg twice daily for 15 days) or indomethacin (1 mg/kg/day for 15 days) (Abbatiello et al, 1975). In oligospermic patients, chronic treatment with indomethacin or ketoprofen increased seminal sperm concentrations (Padrón & Nodarse, 1979;Barkay et ai, 1984), whereas in normospermic volunteers, non-steroidal anti-inflammatory drugs had no effect on sperm density or total sperm output (Freixa et al, 1984; (Boyd, 1970;Jacqueson et al, 1984;Neumann, 1984), but this is apparently a non-specific part of a toxicity syndrome known from many drugs and chemicals which exert no effects on PG synthesis (Neumann, 1984). Testicular prostaglandins seem to reduce spermatogenesis also in rabbits as indicated by data showing that intrascrotal deposition of PGF-2a caused a significant reduction in sperm number per ejaculate and induced temporary sterility (Saksena & Lau, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of naproxen to volun¬ teers for 2 weeks also did not significantly influence sperm motility, although the concentration of seminal PGs was reduced by more than 70% (Bendvold et ai, 1985). In oligospermic patients, chronic treatment with indomethacin or ketoprofen even increased sperm motility (Padrón & Nodarse, 1979;Barkay et ai, 1984). In fact, as in the present experiments with phenylbutazone, treatment with indomethacin and ketoprofen seemed to increase male fertility (Barkay et al, 1984) and it was suggested that non-steroidal anti-inflammatory drugs may have a beneficial effect in the therapy of male infertility (Padrón & Nodarse, 1979;Barkay et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation